Women, irrigation and social norms in Egypt: "The more things change, the more they stay the same" - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2018)
Presented by Dina Najjar (ICARDA), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.